POPULATION CHARACTERISTICS OF THE GODAVARY HILSA OVER THE YEARS 1963-1967 - Rajyalakshmi, T (Indian Journal of Fisheries, 2011)
Hilsa ilisha (Hamilton) constitutes a fishery of some magnitude in almostall the river systems and estuaries of India. It migrates into the freshwatersections of rivers to spawn. In the rivers where it forms a major fishery, muchprogress has been made in delimitirig the areas of spawning, by loeating areas ofegg and larval concentrations (Ravish Chandra, 1962).